1999
DOI: 10.1038/sj.onc.1202892
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed BCL6 (LAZ3) oncoprotein triggers apoptosis, delays S phase progression and associates with replication foci

Abstract: One of the most frequent genetic abnormalities associated with non Hodgkin lymphoma is the structural alteration of the 5' non coding/regulatory region of the BCL6 (LAZ3) protooncogene. BCL6 encodes a POZ/ Zn ®nger protein, a structure similar to that of many Drosophila developmental regulators and to another protein involved in a human hematopoietic malignancy, PLZF. BCL6 is a sequence speci®c transcriptional repressor controlling germinal center formation and T cell dependent immune response. Although the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 66 publications
4
74
0
Order By: Relevance
“…Such assumption is supported by the detection of several endogenous components of the replication apparatus within or near the BCL6 bodies (Albagli et al, 1999; this work and data not shown). However, it implies that the interaction between RF and BCL6 bodies precedes the synthesis DNA by the RF.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Such assumption is supported by the detection of several endogenous components of the replication apparatus within or near the BCL6 bodies (Albagli et al, 1999; this work and data not shown). However, it implies that the interaction between RF and BCL6 bodies precedes the synthesis DNA by the RF.…”
Section: Discussionsupporting
confidence: 55%
“…Human UTA-L cells (Albagli et al, 1999) were grown at 37°C in growth medium (GM) that is a 50/50 mixture of DMEM/F12 medium (Gibco-BRL) containing 10% fetal calf serum (Sigma-Aldrich, Saint Quentin Fallavier, France). The routine culture of the cells was done in GM supplemented gentamycine (PAA, 20 g/ml), tetracycline (Sigma-Aldrich, 2 g/ml), G418 (Gibco-BRL, 500 g/ml), and puromycine (Sigma-Aldrich, 1 g/ml).…”
Section: Materials and Methods Cell Cultures And Nucleic Acid Labelinmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to bcl6, the data in the literature indicate that its role as promotor or inhibitor of apoptosis may depend on the cellular context and the experimental approach (37,(41)(42)(43)(44)(45)(46). Some studies reported that bcl6 may protect cells from apoptosis (41,43,45).…”
Section: Discussionmentioning
confidence: 99%